2017
DOI: 10.3389/fneur.2017.00655
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Onabotulinum Treatment after the First Two Cycles Might Not Be Justified: Results of a Real-life Monocentric Prospective Study in Chronic Migraine

Abstract: Introduction Onabotulinum toxin A (OnabotA) cyclic treatment is approved for the prophylactic treatment of chronic migraine (CM), a highly disabling disorder. Although treatment response varies among patients, current guidelines suggest to stop treatment after cycle 2 if no response is achieved. This prospective study aimed to define, in real-life setting, the evolution of the response to OnabotA over five cycles of treatment among patients non-responding to cycle 1. The results of this study migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…3.3 ). In addition, a small real-world from Europe [ 80 ] has reported a delayed and progressively beneficial effect among patients who continue to receive treatment after failing to respond to the first cycle; this supports the notion that at least another one to two cycles should be attempted before deeming those individuals who do not respond initially to be nonresponders [ 81 ].…”
Section: Place Of Onabotulinumtoxina In the Prevention Of Chronic Migmentioning
confidence: 75%
“…3.3 ). In addition, a small real-world from Europe [ 80 ] has reported a delayed and progressively beneficial effect among patients who continue to receive treatment after failing to respond to the first cycle; this supports the notion that at least another one to two cycles should be attempted before deeming those individuals who do not respond initially to be nonresponders [ 81 ].…”
Section: Place Of Onabotulinumtoxina In the Prevention Of Chronic Migmentioning
confidence: 75%
“…Spanish experts recommendations for the use of OnabotA stated that the first procedure should be performed according to the PREEMPT paradigm, administering 155 Units and in case of lack of response, dose could be increased up to 195 Units in the first three procedures [19]. We found that in certain cases, neurologists admitted to using lesser or higher doses.…”
Section: Discussionmentioning
confidence: 91%
“…To date, some real‐life studies addressed the evolution of CM patients undergoing only 2 OBT‐A sessions instead of one‐year treatment. A monocentric real‐life study by Sarchielli et al reported the evolution in response to OBT‐A repeated cycles among 56 patients non‐responding to cycle 1. The authors demonstrated that Responders (they considered 50% of reduction in headache frequency) progressively increased cycle after cycle (up to 5) and concluded that clinicians should prosecute OBT‐A to guarantee an effective therapeutic option.…”
Section: Discussionmentioning
confidence: 99%